Psychological Support for the Mental Toughness of Tae Kwon Do Athletes - Wibowo, Danan Satriyo; Sulaiman, Ahmad; Akbar, Jepri (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
The winning mentality is still a problem for some athletes in professional competitions, where competing to be the best in a match (championship) is the maximum achievement that an athlete can give as a result of the training process that has been undertaken and the achievement of being the championship winner of a match. The urgency of this research is to measure the influence of psychological support received by athletes on the formation of a winning mentality in each championship they participate in as a form of achieving the need for achievement and self-actualization of the athlete's abilities. This research aims to examine the influence of psychological support on the formation of a winning mentality for Tae Kwon-Do athletes. This research was carried out using a quantitative approach with simple regression analysis to test the hypothesis. The research sample was Bondowoso Tae Kwon-Do athletes who had participated in competitions of at least level. Besuki Ex-Residency region. The measuring instruments used are a psychological support scale and a champion's mental scale. The research results obtained were that psychological support had an influence in forming a winning mentality in Tae Kwon Do athletes. Psychological support can influence a person's mental state so that he can overcome the tension that occurs within him. Social support that comes from support and the social environment can reduce the stress experienced by a person, in this case the athlete's condition. Psychological support will create feelings of being loved, appreciated and not alone in facing the match.The winning mentality is still a problem for some athletes in professional competitions, where competing to be the best in a match (championship) is the maximum achievement that an athlete can give as a result of the training process that has been undertaken and the achievement of being the championship winner of a match. The urgency of this research is to measure the influence of psychological support received by athletes on the formation of a winning mentality in each championship they participate in as a form of achieving the need for achievement and self-actualization of the athlete's abilities. This research aims to examine the influence of psychological support on the formation of a winning mentality for Tae Kwon-Do athletes. This research was carried out using a quantitative approach with simple regression analysis to test the hypothesis. The research sample was Bondowoso Tae Kwon-Do athletes who had participated in competitions of at least level. Besuki Ex-Residency region. The measuring instruments used are a psychological support scale and a champion's mental scale. The research results obtained were that psychological support had an influence in forming a winning mentality in Tae Kwon Do athletes. Psychological support can influence a person's mental state so that he can overcome the tension that occurs within him. Social support that comes from support and the social environment can reduce the stress experienced by a person, in this case the athlete's condition. Psychological support will create feelings of being loved, appreciated and not alone in facing the match.